UNIVERSITY OF IBADAN LIBRARY COMPETITIVENESS OF COCOA VALUE CHAIN IN SOUTHERN NIGERIA (2016)
Cocoa contributes immensely to Nigeria’s export earnings but it has low domestic value addition. In order to improve this, there is a need to ascertain the competitiveness along cocoa value chain. However, there’s a dearth of information on the competitiveness at each stage of cocoa value chain. The competitiveness of cocoa along the value chain in Southern Nigeria was therefore investigated. Using three-stage sampling procedure, six cocoa producing Local Government Areas (LGAs) were purposively selected from Oyo, Ondo and Cross River states in Southern Nigeria using two LGAs per state. In each LGA, two cocoa producing communities were randomly selected. A total of 250 cocoa farmers and 102 cocoa marketers were randomly selected from the twelve communities proportionate to the number of cocoa farmers and cocoa marketers in each community. Fifty-four cocoa processors were randomly selected from the study area. Structured questionnaire was used to collect data on the participants’ socio-economic characteristics, input and output prices at each stage (production, marketing and processing) of cocoa value chain. At production stage, there are Sharecropped Farmers (SF), Self-Owned Farmers (SOF) and Leased/Rented Farmers (LRF); at marketing stage, there are exporters, Licensed Buying Agents (LiBA) and Local Buying Agents (LoBA), while at processing stage there are Cocoa Butter Processors (CBP), Cocoa Powder Processors (CPP) and Black Soap Processors (BSP). Data were analysed using descriptive statistics, policy analysis matrix and partial equilibrium analysis at α0.05. The working experience of cocoa producers, cocoa marketers and cocoa processors were 23.5±14.1, 18.3±8.3 and 9.2±9.2 years, respectively. At the production stage, SF, SOF and LRF had Private Profit (PP) of ₦468 729.76/ha, ₦397 465.03/ha and ₦331 465.03/ha, respectively while Private Cost Ratio (PCR) were 0.22, 0.24 and 0.25, respectively. The SF, SOF and LRF had Social Profit (SP) of ₦792 038.37, ₦536 178.10 and ₦468 729.76, respectively. Also, SF, SOF and LRF had Nominal Protection Coefficient (NPC) of 0.75, 0.85 and 0.79, respectively. At the marketing stage, exporters, LiBA and LoBA had PP and PCR of ₦43 018.01/tonne, ₦36 104.98/tonne, ₦24 279.81/tonne and 0.18, 0.27, 0.40, respectively. Exporters had the highest SP of ₦51 159.04/tonne while exporters, LiBA and LoBA had NPC of 0.98, 0.94 and 0.90, respectively. At the processing stage, CBP, CPP and BSP had PP and PCR of ₦730 229.77/tonne, ₦309 708.13/tonne, ₦92 262.26/tonne and 0.02, 0.05 and 0.27, respectively. The CBP had the highest SP of ₦814 273.32/tonne and lowest Domestic Resource Cost of 0.02. The NPC of 0.95, 0.94 and 0.79 for CBP, UNIVERSITY OF IBADAN LIBRARY iv CPP and BSP, respectively showed lack of fiscal policies’ protection on cocoa processing. Welfare loss of producers was ₦429 432.36/tonne, while consumers’ gain was ₦123 492.22/tonne in the value chain. Competitiveness and comparative advantage along the stages of cocoa value chain exist in Southern Nigeria. The most competitive stage is cocoa processing. Cocoa production, marketing and processing were profitable to cocoa stakeholders in the study area. It is recommended that input use efficiency technologies should be introduced to maintain the competitiveness along the entire cocoa value chain. Keywords: Cocoa value chain, Social cost benefit, Comparative advantage, Effective protection coefficient. Word count: 497